Risks associated with aircraft maintenance in European commercial air transport - Hieminga, Jelle; Turkoglu, Cengiz (EDP Sciences, 2019)
In the 2016 EASA Annual Safety Report, 1318 incidents were categorised as involving a safety issue related to aircraft maintenance. All the Key Risk Areas, or most frequent outcomes, for aircraft maintenance as a safety issue were shown to be related but associated Rulemaking Tasks have not yet appeared in the 2017-2021 European Plan for Aviation Safety. Categorising EU-wide incident reports appears to be difficult due to the use and construction of the ‘Event Types’, or contributing causes, taxonomy used in the reporting tool. Previously developed taxonomies are either limited in the number of categories due to limited information in reports, or they are aimed more at an investigation than straight reporting. As a result, these taxonomies are not suited for use in a reporting tool, and these taxonomies lack the detail for focused feedback to the maintenance industry. Thus, a two-level taxonomy has been developed within this study, using a high-level overview of the maintenance process as a basis for the first level and a variation of descriptions, both specific and more broad-spectrum, for the second level. A set of 3910 incident reports from the central repository were analysed, causing 2677 incidents to be excluded for a variety of reasons such as a lack of information (the narrative was empty in 1100 reports or 28%), or the use of a language other than English (814 incidents, 21%). The remaining 1232 incident reports were categorised using the new taxonomy. Of these, 361 incidents occurred during installation of components (29%) and 308 incidents were related to maintenance control (25%). The increased level of detail from the new taxonomy allows for identification of procedure types that are more susceptible to errors, such as installing or removing components or deferral of a defect so that an aircraft can be dispatched. This will hopefully lead to increased vigilance as well as further measures to increase safety.
Keywords: Aviation Maintenance; Aviation Safety; Continuing Airworthiness